Planificación y diseño de una tienda de calzado denominada Passarela Bellasol” ubicada en la zona central de la ciudad de Loja, aplicando estilo funcional –urbano - Armijos Quiroga, Elsa Marlene (2016)
This research topic called "Planning and interior design of a shoe store called" PASSARELA Bellasol "located in the central area of Loja, using functional style - urban" made in technology in Interior Design at the National University of Loja. The project is aimed at solving problems related to interior culture, art, aesthetics and functionality, specifically interior of shoe stores. Loja Being a city that is economically dependent on some form of trade, decoration and interior design plays a fundamental role in this field, so that the problem of using the interior as a marketing tool comes as a shoe store intervene has no right to its function conditioning. This research is a progressive development of stages that starts from the bibliographic compilation and review of programming and interior design proposals aim at allowing the resolution of functional aesthetic problems. The design process of deductive and inductive rational thoughts, the same that apply at three stages: knowledge, programming and / or processing and design.